The Effect of Internal and External Factors of Companies on Profitability and its Implications on Stock Price Index of State-Owned Banks - Artha, I Wayan Budi; Mulyana, Bambang (The Economics and Finance Letters, 2018)
This study aims to determine the effect of internal factors of the company (CAR, NPL, NIM, BOPO and CASA) and external factors of the company (inflation, economic growth and BI reference interest rates), both partially and jointly on the performance of State-Owned Banks measured with a Return on Assets ratio (ROA) and its implications on the Stock Price Index. The object of research is State-Owned Banks in the period of 2012 - 2017. The sampling technique is saturated sampling, that is, all members of the population are used as samples. The analysis technique used is Panel Data Regression. The results of this study indicate that CAR, NPL, NIM, BOPO, CASA, Inflation, Economic Growth and BI reference interest rate together have a significant effect on ROA. NIM, CASA and BI Reference Interest Rate partially had a positive and significant effect on ROA. BOPO, Inflation and Economic Growth partially have negative and significant effect on ROA. While CAR has a negative effect and NPL has a positive effect, but not significant on ROA. ROA has a negative and significant effect on Stock Price Index of State-Owned Banks.